2020
DOI: 10.1021/acs.inorgchem.9b03545
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing the Intrinsic Antiferromagnetism in Polycrystalline LiCoPO4and LiMnPO4Olivines

Abstract: We report a detailed investigation of the long-range magnetic ordering in polycrystalline samples of LiCoPO4 and LiMnPO4, which belong to a series of well-known olivine cathode materials LiMPO4 (M = Mn, Fe, Co, Ni). Samples were prepared by hydrothermal and solid state methods. The magnetic susceptibility is found to be strongly field-dependent, impacting the antiferromagnetic transition temperature and the bifurcation of the FC and ZFC curves. We discuss the role synthesis conditions have on impurity formatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 74 publications
2
9
0
Order By: Relevance
“…These moments then move closer and closer to the M x and M y of FePO 4 (Table ). While every delithiated sample’s total magnetic moment falls short of the expected 5 μ B , this is consistent with past reports on olivines. , …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These moments then move closer and closer to the M x and M y of FePO 4 (Table ). While every delithiated sample’s total magnetic moment falls short of the expected 5 μ B , this is consistent with past reports on olivines. , …”
Section: Discussionsupporting
confidence: 92%
“…Rousse et al reported the FePO 4 refined magnetic moment to be 4.15 μ B , while the expected is 5 μ B . Gnewuch and Rodriguez found a total moment of 4.28(3) μ B in LiMnPO 4 , while the expected moment is also 5 μ B …”
Section: Discussionmentioning
confidence: 98%
“…The magnetic ordering preference of LCP was calculated to demonstrate the intrinsic antiferromagnetism in LCP. [33] The activation barriers of Li migration were calculated using the CI-NEB method. [34,35] All the lattice parameters were fixed, but all the atomic positions were relaxed within the supercell during the CI-NEB calculations.…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, the compound T bP O 4 [26,27] displays intrinsic bulk magneto-electric effect. A series of polyanionic phosphates LiM P O 4 (M = Mn, Co, Ni or Fe) have aroused special interest to evaluate the associated magnetic behaviour in these minerals [19,[28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%